Reproductive traits of horned octopus Eledone cirrhosa in Atlantic Iberian waters - Regueira, Marcos (2018)
Length–weight relationships, sex-ratio, maturity patterns, size at first maturity, reproductive outputs, fecundity and spawning period of horned octopus Eledone cirrhosa in north-west Iberian coast are presented for the first time. Samples were collected between February 2009 and July 2011 in four fishing ports along the north-west Iberian coast: Burela in north Galician waters (NGW), Ribeira or Bueu in western Galician waters (WGW), and Aveiro in western Portuguese waters (WPW). A total of 4127 individuals (1042 males, 3079 females and six undetermined) were sampled. Individuals ranged from 45 to 191 mm dorsal mantle length (ML) and 15–1159 g body weight (BW). The overall sex-ratio was biased towards females, accounting for 74.71% of whole sample. Main spawning season of this species in north-western Iberian waters extends from May to June. Size at first maturity (ML50%) of males was 108.9 mm in NGW, 99.25 mm in WGW, and 91.4 mm in WPW, whereas ML50% for females were 134.5 mm, 121.4 mm and 100.8 mm, respectively. Potential fecundity was 2452.88 ± 36.4 oocytes per ovary (N = 697). Mean oocyte length was 3.89 ± 0.025 mm (N = 697). The average number of fully developed spermatophores in mature males was 86.55 ± 1.9 (N = 223) with a mean length of 44.97 ± 0.29 mm (N = 224). Potential fecundity in females was significantly (P < 0.05) correlated with ML and BW. Results obtained suggest that energy for gonad growth comes from the diet rather than endogenous reserves.